Prevalence of methicillin-resistant coagulase-negative staphylococci in Africa: a systematic review and meta-analysis - Tomiwa Olumide Adesoji; Namwin Siourime Somda; Patience Tetteh-Quarcoo; Adebayo Osagie Shittu; Eric Sampane Donkor (BMC Infectious Diseases)
Abstract Coagulase-negative staphylococci (CoNS) represent a diverse group of opportunistic pathogens associated with human and animal infections. The burden of infectious diseases attributed to antibiotic-resistant CoNS, particularly methicillin-resistant CoNS (MR-CoNS), is a global public health concern. However, there is limited data on the epidemiology of MR-CoNS in Africa. This systematic review provides insights on MR-CoNS from human and non-human sources in Africa, the methicillin-resistance gene determinants and the associated mobile genetic elements. The review retrieved articles from four electronic databases: PubMed, Scopus, Web of Science, and Google Scholar, using specific keywords. This study was carried out until 20 November 2024. Articles were screened and data was extracted and analyzed following the PRISMA guidelines. The meta-analysis used the binary random effects model with a 95% confidence interval. Overall, 65 articles from 16 African countries were included in the study. The pooled prevalence rates for CoNS and MR-CoNS in Africa were 27% and 36%, respectively. The review identified 36 species of CoNS from human and non-human sources. In addition, 20 (31%) studies each reported CoNS and MR-CoNS from human and animal infections. The most prevalent species of MR-CoNS included Staphylococcus epidermidis, Staphylococcus haemolyticus, and Mammaliicoccus sciuri. The African MR-CoNS harboured different staphylococcal chromosome cassette mec (SCCmec) elements (types I, II, III, IV, V, VI, VIII, and a SCCmec-mecC (hybrid), and the most common SCCmec element was the SCCmec type IV. The findings highlight the paucity of data on the epidemiology of MR-CoNS in Africa. The identification of MR-CoNS from human and animal infections indicates the need for a detailed characterization using molecular methods. This strategy will provide data to healthcare practitioners and policymakers to develop effective measures to combat antimicrobial resistance in Africa.